Crystalline morphology of thermoplastic starch/talc nanocomposites induced by thermal processing. Issue 6 (June 2019) - Castillo, Luciana A.; López, Olivia V.; García, María A.; Barbosa, Silvia E.; Villar, Marcelo A.
Abstract: A structural study about the changes induced by plasticization of native corn starch was carried out in this work. The influence of talc nanoparticles presence during starch thermal processing was also evaluated. Macroscopic observation of the granules appearance evolution during melt-mixing and thermo-compression was supported by a theoretical description related to these processing methods. Melt-mixing induced a polymorphic transformation from A- to Vh -type and a reduction in the degree of crystallinity. Homogenous appearance of the plasticized starch was in accordance to the disruption of granules integrity, evidenced by SEM. This observation agreed to the distinctive XRD pattern of plasticized starch from unprocessed granules. Talc incorporation did not require the adjustment of processing parameters in order to obtain a homogenous thermoplastic material, with an adequate particles distribution within the matrix. Regardless talc presence, plasticized starch presented a Vh -type crystalline structure. Thermo-compression led to particles alignment promoted by talc laminar morphology.